Complete training for DaVinci Resolve - Hullfish, Steve; Silga, Bob.; Safari eBooks ([S.l.] : Class on Demand, 2012)
"Blackmagic Design's DaVinci Resolve draws on a rich heritage of color grading expertise and technology to deliver an outstanding grading product. Learn how to get the best out of your Resolve software with world-class training. Leveraging Steve Hullfish's expertise, Bob Sliga's brilliance as a color-grader, and Class on Demand's state-of-the-art on-demand training platform, this training is sure to get you up to speed quickly and easily."--Resource description page.
Title from resource description page (viewed June 10, 2013).
Presenters, Steve Hullfish, Bob Silga.
Keywords: DiVinci Resolve; Motion pictures -- Editing -- Data processing; Digital video -- Editing -- Data processing; Color; Electronic books